Gladiators and the story of the Colosseum - Saunders, Nicholas J. (Columbus, OH : School Specialty Pub., 2006)
Provides an introduction to the Roman Empire, discusses the building of the Colosseum, and looks at how gladiators were chosen, what gladiator's lives were like, the practice of killing Christians in the arena, and the Colosseum's decline. Presented in graphic novel format.
Includes index.
4.6
3-6
Keywords: Gladiators -- Comic books, strips, etc. -- Juvenile literature; Rome -- Social life and customs -- Comic books, strips, etc. -- Juvenile literature; Colosseum (Rome, Italy) -- Comic books, strips, etc. -- Juvenile literature; Gladiators -- Cartoons and comics; Rome -- Social life and customs -- Cartoons and comics; Colosseum (Rome, Italy) -- Cartoons and comics; Cartoons and comics; Gladiators -- Comic books, strips, etc; Rome -- Social life and customs -- Comic books, strips, etc; Colosseum (Rome, Italy) -- Comic books, strips, etc; Comic books, strips, etc